(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Wild edible plants have gained attention due to growing concerns for global food security.Nutrient contents are frequently determined for wild edible plants identified from ethnobotanical surveys.In this article, we conducted an ethnobotanical survey at the study site and collected twenty-one wild plants for evaluating their relative nutrient indices. Our results suggested that the tubers of Colocasia esculenta hadthe highest macronutrients, fruits of Spondias pinnata had high vitamins, the leaves of Colocasia esculenta and Chenopodium giganteum had high dietary fibres, and leaves of Digera muricatawere rich in minerals. Thus, these plants can offer a basis for developing dietary supplements and nutraceuticals on a commercial scale, which may help in achievingthe sustainable development goal of zero hunger.